Association between Matrix Metalloproteinase-3 Gene Polymorphism and Susceptibility to Chronic Periodontitis: A systematic review and meta-analysis: Gene Polymorphism and Chronic Periodontitis: Meta-Analysis - Hu, Ankang; Wang, Xin; Ai, Lisi; Liu, Kun; Kong, Lingxue (Journal of Medical Biochemistry, 2024)
Background: This study aimed to explore the correlation between the MMP-3 1171 5A/6A gene polymorphism and susceptibility to Chronic Periodontitis (CP). Methods: Following the PRISMA guidelines, a systematic search was conducted across four electronic databases (PubMed, Embase, Web of Science, and Cochrane Library) without any time or language limitations. The selection criteria included case-control studies examining the association between the MMP-3 gene polymorphism and CP. The data were independently extracted and cross-checked by two reviewers. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the studies. Statistical heterogeneity and publication bias were assessed. Results: Five studies, published between 2004 and 2019, met the inclusion criteria for the meta-analysis. No significant association was observed between MMP-3 gene polymorphism and CP susceptibility across all subjects in the four gene models. However, subgroup analysis revealed significant differences based on genotyping methods and smoking habits. Using PCR-RFLP genotyping method, the allele and additive models showed a positive correlation with the risk of CP (5A vs 6A, OR=1.12, 95%CI (1.02 1.23); 5A5A vs 6A6A, OR=2.85, 95%CI (1.61 4.86)). In contrast, using Sanger sequencing method, the 5A mutation appeared to reduce CP susceptibility (5A vs 6A, OR=0.77, 95%CI (0.67 0.87); 5A5A vs 6A6A, OR=0.20, 95%CI (0.09 0.42)). Moreover, smoking habits appeared to modulate the risk. Among smokers, the 5A mutation increased susceptibility to CP, while among non-smokers it decreased. Conclusions: While no significant correlation was found in the overall population, the stratified analysis revealed nuanced relationships contingent on genotyping methods and smoking habits.